DPPH free radical scavenging activity and ferric reducing power of Lato (Caulerpa lentillifera) and gulaman (Hypnea esperi). - Pamaylaon, Elaine Grace A. (2019.)
Antioxidants in biological systems have multiple functions such as reducing oxidative damage in the major signaling pathways of cells. Globally, several research studies have reported that seaweeds are rich sources of phytochemical compounds having antioxidant potential. Western Visayas is among the top five seaweed producers in the country. Hence, this study evaluated the antioxidant potential of two common edible species of green and red seaweeds found in Panay, namely, Caulerpa lentillifera, commonly known as Lato and Hypnea esperi, commonly known as Gulaman using DPPH free radical-scavenging activity and ferric reducing antioxidant power assays. Phytochemical screening was done to evaluate the phytochemical profile of the algal extracts. Furthermore, the bioactive fractions with antioxidant character were characterized using TLC-DPPH bioautography coupled with FTIR analysis. Results of the DPPH-free radical scavenging assay showed that H. esperi exhibited higher radical scavenging activity (~62%) than C. lentillifera (~30%) at 200 ppm. Similarly, H. esperi also showed higher ferric reducing power denoted by a higher absorbance (~0.2157) of the formed complex at 700 nm. Results of the TLC-DPPH bioautography showed that H. esperi have more bioactive fractions having antioxidant property compared with C. lentillifera. This is consistent with the observed antioxidant potential of the algal extracts in which H. esperi have higher DPPH-free radical scavenging activity and higher ferric reducing power. The FTIR profile of the extracts showed the presence of hydroxyl, carbonyl, esters, and aromatic groups which suggests the presence of O-containing phytochemical compounds like flavonoids, coumarins, and terpenoids as observed in the phytochemical screening. In relation with the TLC-DPPH profile of the algal extracts, results of the FTIR analysis also suggest that the compounds responsible for the antioxidant activity might possess a polar property due to the presence of polar hydroxyl and carbonyl groups. The compounds also had a low Rf value of 0.025 supporting the polarity claim. Results of this study suggest that these seaweed species can be a potential source of natural antioxidants.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Lato; Caulerpa lentillifera; Gulaman; Hypnea esperi